Committed Brokers: união entre prefeitos e deputados no Brasil - Felipe Lima Eduardo (2016)
The relationship between mayors and deputies, in the Brazilian politics, goes beyond the electoral support, comprising a commitment relation. Although this relation is not well captured by the Brazilian literature, the dissertation shows that it is important for the functioning of the representative system, since the mayors work as brokers of the deputies and, vice versa, the deputies work as brokers of the mayors. The dissertation uses a unique set of data in order to show the importance of the union between them and how a positive evaluation of one can interfere in the electoral performance of the other. In addition to describing and confirming the alliance between mayors and deputies, the dissertation also verifies, through survey experiments, how the distribution of individual and collective goods, provided by the alliance, affects the chance of votes for mayor candidates. The dissertation uses data from opinion polls with deputies and voters, focus groups, election results and a set of survey experiments conducted in the Brazilian municipal elections in 2016.